PENGARUH BUDAYA SEKOLAH, INTEGRITAS GURU DAN KEPUASAN KERJA GURU TERHADAP EFEKTIVITAS KERJA GURU SMKN KABUPATEN KUBU RAYA - Mujiono Mujiono (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2017)
The research objective to observe the influence of school culture, integrity teachers and teacher job satisfaction on the effectiveness of teachers' work. The study was conducted in the Education Kubu Raya district area Kalimantan West, methods of field research through surveys, using questionnaires through path analysis approach. Affordable population is around the Kubu Raya teachers of SMKN using random sampling techniques. The results obtained are positive effect School culture on the effectiveness of teacher work, the integrity of the teacher toward teacher effectiveness, teacher job satisfaction toward effectiveness of teacher work, school culture toward job satisfaction of teachers, the integrity of the teacher toward teacher job satisfaction, and a positive effect the school culture toward integrity of teachers. In the end the results of this research are expected to be useful for education and to increase the effectiveness of teachers SMKN (vocational schools) in Kubu Raya Kalimantan West